Polyamine regulates tolerance to water stress in leaves of white clover associated with antioxidant defense and dehydrin genes via involvement in calcium messenger system and hydrogen peroxide signaling - Li, Zhou; Zhang, Yan; Peng, Dandan; Wang, Xiaojuan; Peng, Yan; He, Xiaoshuang; Zhang, Xinquan; Ma, Xiao; Huang, Linkai; Yan, Yanhong (Frontiers in Physiology, 2015)
Endogenous polyamine (PA) may play a critical role in tolerance to water stress in plants acting as a signaling molecule activator. Water stress caused increases in endogenous PA content in leaves, including putrescine (Put), spermidine (Spd), and spermine (Spm). Exogenous application of Spd could induce the instantaneous H2O2 burst and accumulation of cytosolic free Ca2+, and activate NADPH oxidase and CDPK gene expression in cells. To a great extent, PA biosynthetic inhibitor reduced the water stress-induced H2O2 accumulation, free cytosolic Ca2+ release, antioxidant enzyme activities and genes expression leading to aggravate water stress-induced oxidative damage, while these suppressing effects were alleviated by the addition of exogenous Spd, indicating PA was involved in water stress-induced H2O2 and cytosolic free Ca2+ production as well as stress tolerance. Dehydrin genes (Y2SK, Y2K, and SK2) were showed to be highly responsive to exogenous Spd. PA-induced antioxidant defense and dehydrin genes expression could be blocked by the scavenger of H2O2 and the inhibitors of H2O2 generation or Ca2+ channels blockers, a calmodulin antagonist, as well as the inhibitor of CDPK. These findings suggested that PA regulated tolerance to water stress in white clover associated with antioxidant defenses and dehydrins via involvement in the calcium messenger system and H2O2 signaling pathways. PA-induced H2O2 production required Ca2+ release, while PA-induced Ca2+ release was also essential for H2O2 production, suggesting an interaction between PA-induced H2O2 and Ca2+ signaling.